2017
DOI: 10.1159/000479555
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adjuvant Treatment with Entacapone in Advanced Parkinson’s Disease with Motor Fluctuation: A Systematic Meta-Analysis

Abstract: Aims:To assess the efficacy and safety of adjuvant treatment with entacapone in the treatment of later Parkinson's disease (PD) patients with motor fluctuation. Methods: We conducted a systematic review of relevant studies from 8 databases to June 23, 2016. Results: Fourteen studies were included in this review (n = 2,804). The results showed that compared with placebo, adjuvant therapy with entacapone significantly increased on time (p < 0.01) and reduced off time (p < 0.01), the required levodopa (LD) dose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“… 26 A meta-analysis of 14 studies also indicated adjuvant treatment with entacapone improved UPDRS ADL and motor scores. 27 Considering the fact that entacapone can increase levodopa sustainability by extending the drug’s half-life, it was reasonable to find that LCE improved scores of UPDRS II and UPDRS III in our study, which is also consistent with previous findings. Three published RCTs with a minimum 3-month follow-up suggested that levodopa with entacapone had a slightly beneficial effect on patient QoL, but at a low level.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 26 A meta-analysis of 14 studies also indicated adjuvant treatment with entacapone improved UPDRS ADL and motor scores. 27 Considering the fact that entacapone can increase levodopa sustainability by extending the drug’s half-life, it was reasonable to find that LCE improved scores of UPDRS II and UPDRS III in our study, which is also consistent with previous findings. Three published RCTs with a minimum 3-month follow-up suggested that levodopa with entacapone had a slightly beneficial effect on patient QoL, but at a low level.…”
Section: Discussionsupporting
confidence: 92%
“…Risks of total AEs and single AEs were higher in the LCE group, but all were noted in the package insert and published articles on entacapone. 27 Such adverse reactions to entacapone are supposed to be associated with enhanced dopamine activity. Urine abnormality was the most commonly reported AE in the LCE group, but this is a benign event related to the color of entacapone metabolites eliminated in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we planned to also synthesize tyrosol and homovanillyl alcohol hybrids to evaluate the influence of the ortho -diphenolic moiety in the tested biological activities. Noteworthy is the presence of a nitrocatechol moiety in two catechol O -methyltransferase (COMT) inhibitors such as tolcapone and entacapone, included in the clinical treatment of PD ( Li et al, 2017 ; Artusi et al, 2021 ). Furthermore, several studies demonstrated a remarkable activity of nitro-HT derivatives in the dopamine metabolism, suggesting a putative effect against PD as novel and lipophilic COMT inhibitors ( Gallardo et al, 2014 ; Trujillo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis done with 14 studies to compare the effectiveness and safety of adjuvant treatment of entacapone in PD, a trend towards increased patient withdrawal was found due to intolerable adverse events. Patients on entacapone had a higher frequency of adverse events than those on placebo ( Li et al., 2017 ). Although it is hypothesized that these adverse events may be related to the increase of dopamine caused by entacapone in the corpus striatum ( Li et al., 2017 ), the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients on entacapone had a higher frequency of adverse events than those on placebo ( Li et al., 2017 ). Although it is hypothesized that these adverse events may be related to the increase of dopamine caused by entacapone in the corpus striatum ( Li et al., 2017 ), the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%